Diagnosis and Management of Classical Homocystinuria in Brazil: A Summary of 72 Late-Diagnosed Patients. (7th August 2018) - Poloni, Soraia; Hoss, Giovana W.; Sperb-Ludwig, Fernanda; Borsatto, Taciane; Doriqui, Maria Juliana R.; Leão, Emília K.E.A; Boa-Sorte, Ney; Lourenço, Charles M.; Kim, Chong A.; de Souza, Carolina F. M.; Rocha, Helio; Ribeiro, Marcia; et al.
This study described a broad clinical characterization of classical homocystinuria (HCU) in Brazil. This was a cross-sectional, observational study including clinical and biochemical data from 72 patients (60 families) from Brazil (South, n = 13; Southeast, n = 37; Northeast, n = 8; North, n = 1; and Midwest, n = 1). Parental consanguinity was reported in 42% of families. Ocular manifestations were the earliest detected symptom (53% of cases), the main reason for diagnostic suspicion (63% of cases), and the most prevalent manifestation at diagnosis (67% of cases). Pyridoxine responsiveness was observed in 14% of patients. Only 22% of nonresponsive patients on treatment had total homocysteine levels <100 µmol/L. Most commonly used treatment strategies were pyridoxine (93% of patients), folic acid (90%), betaine (74%), vitamin B12 (27%), and low-methionine diet + metabolic formula (17%). Most patients diagnosed with HCU in Brazil are late diagnosed, express a severe phenotype, and poor metabolic control. Milder forms of HCU are likely underrepresented due to underdiagnosis.